Motivations and consequences of U.S. IPOs by Chinese firms - Oh, Bing Quan (Nanyang Technological University, 2022)
With the passing of the Holding Foreign Companies Accountable Act, U.S.-listed Chinese companies (ULCC) find themselves once again in the crosshairs of the U.S. Securities and Exchange Commission. We examine the motivations and consequences of U.S. IPOs by Chinese firms through an endogenous treatment effects analysis on firm valuation. We contribute to the literature by finding new developments in the Chinese listing decision using a dataset of privately held Chinese firms. This comprises a sample of 169 ULCCs against a control sample of 2048 China-listed Chinese companies (CLCC). We identify three reasons for a Chinese U.S. listing: (1) out of necessity for unprofitable firms, (2) influence by foreign providers of capital, (3) as a corporate strategy to boost their reputation. Contrary to foreign listing theory, a foreign listing discount is observed. The average Tobin's q of a Chinese firm drops by 1.399 in a year's time if it chooses to list in the U.S. instead of China. This finding is robust across different estimators and valuation measures. The valuation gap is attributed to the variable interest entity (VIE) structure used by most ULCCs which increases their risk premium, and also to the finding that ULCCs continue to be stigmatized by U.S. investors.